Resistance training intervention performed with different muscle action durations influences the maximal dynamic strength without promoting joint-angle specific strength gains. Issue 21 (2nd November 2021) - Diniz, Rodrigo César Ribeiro; Tourino, Frank Douglas; Lacerda, Lucas Túlio de; Martins Costa, Hugo Cesar; Lanza, Marcel Bahia; Pedrosa, Gustavo Ferreira; Lima, Fernando Vitor; Chagas, Mauro Heleno
ABSTRACT: The present study investigated the effect of 10-week matched (range of motion, volume, intensity, rest, and repetition duration) training protocols with varying muscle action duration (MAD) on maximal voluntary isometric contraction (MVIC) test at eight different knee angles and one-repetition maximum (1RM) test after in seated knee extensor machine. Forty women were allocated into one control and three training groups with varying MAD: 5C1E (5s concentric action [CON] and 1s eccentric action [ECC]), 3C3E (3s CON and 3s ECC), and 1C5E (1s CON and 5s ECC). All training groups (5C1E, 3C3E, and 1C5E) showed a greater relative response in 1RM performance than the control group (0.1 ± 3.5%, p ≤ 0.05). The 1C5E group presented greater relative increases in the 1RM performance (22.1 ± 11.6%) compared to 5C1E (13.6 ± 9.2%; p ≤ 0.05) and 3C3E (14.1 ± 5.5%, p ≤ 0.05) groups. The training groups increased the MVIC performance more than the control group (p ≤ 0.05), although there were no significant differences between the training groups. This study demonstrated that isoinertial resistance training protocols with shorter CON MAD showed greater maximum dynamic strength performance response than matched training protocols with other MAD configurations. However, the configuration of MAD did not induce angle-specificity to increase the maximum isometric strength.